2019
DOI: 10.1038/s41419-019-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of RhoA geranylgeranylation and Ras farnesylation breaks the integrity of the blood–testis barrier and results in hypospermatogenesis

Abstract: Non-obstructive azoospermia (NOA) severely affects male infertility, however, the deep mechanisms of this disease are rarely interpreted. In this study, we find that undifferentiated spermatogonial stem cells (SSCs) still exist in the basal compartment of the seminiferous tubules and the blood–testis barrier (BTB) formed by the interaction of neighbor Sertoli cells (SCs) is incomplete in NOA patients with spermatogenic maturation arrest. The adhesions between SCs and germ cells (GCs) are also broken in NOA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Sertoli cell TJs and TJ proteins might be regulated by FSH, testosterone, and paracrine hormones as possible mediators of junction formation and disassembly during the translocation process ( Stanton, 2016 ). These biological breakthroughs have resulted in a slew of new technical advancements in the treatment of male infertility, including the repair of damaged BTB in nonobstructive azoospermia (NOA) patients with spermatogenic maturation arrest and hypospermatogenesis ( Zhu et al, 2019 ) and manipulation of TJ proteins to promote stem cell homing efficiency ( Kanatsu-Shinohara et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sertoli cell TJs and TJ proteins might be regulated by FSH, testosterone, and paracrine hormones as possible mediators of junction formation and disassembly during the translocation process ( Stanton, 2016 ). These biological breakthroughs have resulted in a slew of new technical advancements in the treatment of male infertility, including the repair of damaged BTB in nonobstructive azoospermia (NOA) patients with spermatogenic maturation arrest and hypospermatogenesis ( Zhu et al, 2019 ) and manipulation of TJ proteins to promote stem cell homing efficiency ( Kanatsu-Shinohara et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytospermia is an established marker of inflammation and it has been associated with increased semen levels of interleukin-6 and tumor necrosis factor-α, both inflammatory cytokines, in infertile patients [ 27 ]. Leukocytes are also involved in the pathogenesis of autoimmune inflammation of seminal ducts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the Human Protein Atlas, GGPS1 expression is highest in the testis which may be related to the essential role of GGDPS in spermatogenesis. 35 , 41 , 42 Expression levels also appear elevated in the eye, skeletal muscle and breast tissue, suggesting that GGDPS may play an important role in these tissues as well. While previous studies have found elevated levels of geranylgeranylated proteins in the human heart, brain, skeletal muscle and testis, variation between geranylgeranylated protein levels and GGPS1 tissue expression may indicate that expression of the synthase does not necessarily correlate with levels of geranylgeranylated proteins.…”
Section: Ggdps Expression and Known Mutationsmentioning
confidence: 99%